2016
DOI: 10.1016/j.quaint.2015.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Diatom records in the Quaternary marine sequences around the Japanese Islands

Abstract: Understanding the Quaternary is a key to estimating what the Earth's climate will be like in the future. Such studies demand high-resolution analyses based on the paleoclimatic proxy records of changing the Earth's orbital forcing and solar insolation that affect the climate system. Quaternary diatom biostratigraphy and paleoceanography have been well established based on the Quaternary marine sequences obtained by piston coring and deep-sea drilling around the Japanese Islands. This paper firstly reviews the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, transitional-subtropical water probably did not flow into the Japan Sea from the southern strait. Koizumi and Yamamoto (2016) showed that at the same latitude, the diatom Td'-based sea surface temperature (SST) of the Japan Sea (ODP Site 797) was colder than that recorded in the North Pacific (ODP Site 436) at a similar latitude despite the opening of the seaway into the southern Japan Sea at ca. 3.1 Ma (Iijima and Tada 1990;Tada 1994;Ogasawara 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, transitional-subtropical water probably did not flow into the Japan Sea from the southern strait. Koizumi and Yamamoto (2016) showed that at the same latitude, the diatom Td'-based sea surface temperature (SST) of the Japan Sea (ODP Site 797) was colder than that recorded in the North Pacific (ODP Site 436) at a similar latitude despite the opening of the seaway into the southern Japan Sea at ca. 3.1 Ma (Iijima and Tada 1990;Tada 1994;Ogasawara 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Despite its relatively flat topography, one can observe a series of beach ridges that run between the sandy beach and wetlands. These marine terraces are categorized into four elevations, each corresponding to specific marine isotope stages (MIS) 5e, 7, 9, and 11 [26] (S1 Fig) . During MIS 5e, the marine terraces reach heights of around 55 m, whereas during MIS 7, they rise to approximately 90 m. The height of these marine terraces gradually decreases as one moves westward [27] (S1 Fig) , indicative of a westward tilt. On the eastern side of the Kabari River, these terraces are composed of Neogene sedimentary rocks, such as sandstone and tuffaceous siltstone [27], which have been extensively exposed due to marine erosion and are covered by beach sand.…”
Section: Study Area and Geological Settingsmentioning
confidence: 99%
“…Considering the global GIA, the local uplift of the 125-ka timescale for the Kabari area is 40-50 m [26,29], with an average uplift rate ranging from 0.33-0.40 mm/yr. Applying the GIA model obtained for the Shimokita Peninsula [58], which is less affected by local crustal deformation, to the uplift in this area, a maximum sea level of + 3 m was obtained at 6-4 ka.…”
Section: Estimation Of Relative Sea-level Changementioning
confidence: 99%